Spectroscopic investigation of partial LTE assumption and plasma temperature field in pulsed MAG arcs. (4th June 2018) - Wang, Fei; Cressault, Y; Teulet, Ph; Valensi, F; Li, Huan; Yang, Ke; Yu, Fusheng
Abstract: The study of gas–metal arc welding (GMAW) often relies on the hypothesis of local thermodynamical equilibrium (LTE). Few works are dedicated to its validation and none is focused on the case of pulsed metal active gas welding. This paper presents the result of a spectroscopic diagnostic performed on a pulsed welding arc with 82%Ar–18%CO2 shielding gas. High-speed imaging and electrical data recording are also performed. The excitation temperature is obtained with the Boltzmann plot method, while iron and argon line Stark broadening measurement is used to obtain the electron temperature and density. The iron mole fraction in the plasma is calculated by solving the conservation equations. Partial LTE hypothesis validity across the arc is discussed considering the agreement between the two temperatures, electron density and iron content. The results show supporting evidence for the main part of the plasma, along radial and axial directions. This can be associated with high iron vapour concentration, close to 100% near the consumable anode tip. Discrepancies occur only at the fringe of the arc, where the two temperatures differ by more than 2000 K. The temperature drop close to the arc axis observable for the upper part is weaker when compared with an inert gas welding operation.